PENGEMBANGAN MODUL BERBASIS PROBLEM BASED LEARNING MATERI PERPINDAHAN KALOR MATA PELAJARAN IPA - Khoirunnisa, Ani; Nulhakim, Lukman; Syachruroji, Ahmad (Universitas Muhammadiyah Surakarta, 2020)
The purpose of this research is to develop a module based on problem based learning. This research was conducted at SDN Pegadingan 1 in the 5th grade Natural Sciences subject of heat transfer material contained in basic competencies 3.6. The method used in this research is a research and development method using research and development steps according to Sugiyono. Based on the feasibility test that has been conducted by a team of material experts, design experts, and education experts, an overall average score of 89.06% was obtained which included in the